2023
DOI: 10.21203/rs.3.rs-2683050/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Eye movement defects in KO zebrafish reveals SRPK3 as a causative gene for an X-linked intellectual disability

Abstract: Intellectual disability (ID) is a common neurodevelopmental disorder characterized by significantly impaired intellectual and adaptive functioning. X-linked ID (XLID) disorders, caused by defects in genes on the X chromosome, affect 1.7 out of 1,000 males. Employing exome sequencing, we identified three missense mutations (c.475C > G; p.H159D, c.1373C > A; p.T458N, and c.1585G > A; p.E529K) in the SRPK3 gene in seven XLID patients from three independent families. Clinical features common to the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…Similar upregulation was seen in a knock-in RBM20 mouse model (Rbm20 S637A ) where phosphorylation was impaired 33 . While in our hands the srpk3-null 5-dpf zebrafish appeared normal with almost unaffected fiber structure, at the time of submission an adult KO model was shown to present agenesis of cerebellar structures and abnormal behavior 34 , suggesting srpk3 may also be involved in neural development.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Similar upregulation was seen in a knock-in RBM20 mouse model (Rbm20 S637A ) where phosphorylation was impaired 33 . While in our hands the srpk3-null 5-dpf zebrafish appeared normal with almost unaffected fiber structure, at the time of submission an adult KO model was shown to present agenesis of cerebellar structures and abnormal behavior 34 , suggesting srpk3 may also be involved in neural development.…”
Section: Discussioncontrasting
confidence: 47%
“…59). In fact, SRPK3 has previously been suggested as a causative gene in patients with X-linked spinocerebellar ataxia 60 and intellectual disability 34,61 . Notably, it has been proposed that abnormal SRPK-mediated phosphorylation of an E3 ubiquitin ligase might disrupt neurodevelopmental regulation 45,56 .…”
Section: Articlementioning
confidence: 99%
“… 18 A zebrafish knockout study in which Srpk3 −/− fish were raised to adulthood has recently revealed SRPK3 to be a compelling candidate gene for X‐linked intellectual disability. 19 The impact of its deletion in our patient and two others is unclear, however, due to the early mortality reported in CADDS. 6 , 8 …”
Section: Discussionmentioning
confidence: 72%